Sexual Behavior Increases Cell Proliferation in the Rostral Migratory Stream and Promotes the Differentiation of the New Cells into Neurons in the Accessory Olfactory Bulb of Female Rats - Corona, Rebeca; Retana-Márquez, Socorro; Portillo, Wendy; Paredes, Raúl G. (Frontiers in Neuroscience, 2016)
We have previously demonstrated that 15 days after female rats pace the sexual interaction, there is an increase in the number of new cells that reach the granular cell layer (GrL) of the accessory olfactory bulb (AOB). The aim of the present study was to evaluate if the first sexual experience in the female rat increases cell proliferation in the subventricular zone (SVZ) and the rostral migratory stream (RMS). We also tested if this behavior promotes the survival of the new cells that integrate into the main olfactory bulb (MOB) and AOB 45 days after the behavioral test. Sexually naive female rats were injected with the DNA synthesis marker 5´-bromo-2´-deoxyuridine (BrdU) on the day of the behavioral test. They were randomly divided into the following groups: Female rats placed alone in the mating cage (1); Females exposed to amyl acetate odor (banana scent, 2); Females that could see, hear and smell the male but physical contact was not possible (exposed to male, 3); Female rats that could pace the sexual interaction (4); and females that mated without the possibility of pacing the sexual interaction (5). Animals were sacrificed 2 days after the behavioral test (proliferation) or 45 days later (survival). Our results show that 2 days after females were exposed to banana scent or to the male, they had a higher number of cells in the SVZ. Females that mated in pace and no-paced conditions had more new cells in the RMS. At 45 days, no significant differences were found in the number of new cells that survived in the MOB or in the AOB. However, mating increased the percentage of new cells that differentiated into neurons in the GrL of the AOB. These new cells expressed c-Fos after a second sexual encounter just before the females were sacrificed. No significant differences in plasma levels of estradiol and progesterone were observed between groups. Our results indicate that the first sexual experience increases cell proliferation in the RMS and mating 45 days later enhances the number of new cells that differentiate into neurons in the AOB. These new neurons are activated